Incorporating Principles of Mindfulness in the Design of Technology - Goray, Cami; Jarrahi, Mohammad Hossein (2020)
ABSTRACT The ability to focus is a key skill for today’s knowledge workers. While the COVID-19 pandemic may have presented a host of other types of responsibilities that could impact work focus, such as economic distress or work-life balance, this short paper is specifically focused on digital distraction. As a result of the COVID-19 pandemic upending traditional work routines, the seismic shift to virtual work in the home ignites even more urgency to the conversation about how digital technology can distract or support workers in allocating their attention wisely. This paper contributes to current research in digital distraction (and, more broadly, human-computer interaction) by introducing how the principles of mindfulness can be incorporated in the design of technology, with a focus on intelligent assistants. Keywords Knowledge work, digital distraction, mindfulness, mindful work, mindful design, interaction design, productivity, wellbeing, intelligent assistant ABOUT THE AUTHOR/S Cami Goray University of Michigan at Ann Arbor cami.goray@gmail.com Cami Goray is a doctoral student at the University of Michigan at Ann Arbor. She aims to use her background in user experience research to build technologies that support digital wellbeing. Mohammad Hossein Jarrahi University of North Carolina at Chapel Hill jarrahi@unc.edu Mohammad Hossein Jarrahi is an associate professor at the UNC School of Information and Library Science. Mohammad’s research focuses on the use and consequences of information and communication technologies and the accompanying social and organizational changes. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).